La huerta escolar multiplica las oportunidades - Experiencias del ProHuerta, como un programa sin techo - Vega, Gabriela Fernanda; Lujan, Ricardo Lorenzo; Melidoro, Silvina (Estación Experimental Agropecuaria La Rioja, INTA, 2023)
EEA La Rioja